Pengaruh Konseling Gizi Terhadap Tindakan Ibu Dalam Pemberian MP-ASI Dan Berat Badan Balita Gizi Kurang 6-24 Bulan Di Desa Sesela Wilayah Kerja Puskesmas Gunungsari Kabupaten Lombok Barat - Daniel Nugraha; Abdul Salam; Yuli Laraeni (Poltekkes Kemenkes Mataram, 2017)
Background. Development in Indonesia is basically shown to improve the welfare and security of all Indonesian people. The right of Indonesian citizens to improve their quality of life is the Human Rights (HAM) guaranteed by the Constitution. Giving complementary food for breastmilk that is too early can cause diarrhea so that the weight decreases. One effort to overcome malnutrition is by increasing one's knowledge, attitudes and actions by conducting nutritional counseling. Based on the results of monitoring the nutritional status of West Lombok in 2015, the highest indicator of underweight under-five children in Gunungsari sub-district was 19.80% with the highest BGM cases in the village of Sesela in the Gunungsari Community Health Center as many as 25 children. Research Purposes. The purpose of this study was to determine the effect of nutritional counseling on the actions of women in the provision of MP-ASI and underweight children under five 6-24 months in the Sesela Village of the Gunungsari Community Health Center Working Area. Research Methods. This type of research uses quasi experiment design. The independent variables in this study were nutrition counseling and the dependent variable was maternal action and toddler weight. The sample in this study is toddlers aged 6-24 months by means of nonprobility sampling which means that all populations are sampled. This research took place in January to February 2017. Research Result. Based on the results of statistical tests using the Wilconxon test with the results of the value p = 0.00 <0.05, it can be concluded that there was a significant effect between maternal actions before and after nutritional counseling and the Mann-Whitney Test with p = 0.01 <0.05, it can be concluded that significant between mother's actions towards toddler weight. Conclusion. There is an influence of nutritional counseling on the actions of mothers and toddlers' weight.